2023
DOI: 10.1002/admi.202300721
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Confinement of Dip‐Pen Nanolithography Written Phospholipid Structures on CuZr Nanoglasses

Srivatsan K. Vasantham,
Evgeniy Boltynjuk,
Sree Harsha Nandam
et al.

Abstract: Nanoglasses have attracted considerable interest among material scientists due to their novel and surprising properties. However, there is still a significant gap in understanding how nanoglasses interact with biomaterials and their effects on living cells. Previous cell studies have reported indications of possible proliferation effects, but a comprehensive understanding of differentiating nanoglass influences from distinct material or topography effects is yet to be established. In this study, the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…For the first time, mechanical properties of amorphous alloys may be controlled in a new way, i.e., by alternating their microstructures (Voigt et al, 2023a;2023b;Singh et al, 2023;Vasantham et al, 2023), similar to those applied for crystalline materials, as demonstrated in our previous experimental work (Li et al, 2021a) that the grain-size effects play an important role in tuning the mechanical properties of NGs. From atomistic simulations, Adibi et al (Adibi et al, 2014;2015) have found that the mechanical strength of NGs would decrease monotonously through reducing the size of glassy grains in NGs with a homogenous chemical composition.…”
mentioning
confidence: 88%
“…For the first time, mechanical properties of amorphous alloys may be controlled in a new way, i.e., by alternating their microstructures (Voigt et al, 2023a;2023b;Singh et al, 2023;Vasantham et al, 2023), similar to those applied for crystalline materials, as demonstrated in our previous experimental work (Li et al, 2021a) that the grain-size effects play an important role in tuning the mechanical properties of NGs. From atomistic simulations, Adibi et al (Adibi et al, 2014;2015) have found that the mechanical strength of NGs would decrease monotonously through reducing the size of glassy grains in NGs with a homogenous chemical composition.…”
mentioning
confidence: 88%